Evaluation of Soil and Water Ecological Security for Mining Cities in Anhui Province Based on VIKOR Model - He Gang; Hou Xiaoyu; Wang Xiaodong; Zhao Shuhang (Shuitu baochi tongbao)
[Objective] The status of ecological security in mining cities was determined and the factors restricting the development of ecological security were clarified in order to provide a scientific basis for sustainable mining in Anhui Province. [Methods] A comprehensive evaluation index system based on economy-environment-society was constructed for soil and water ecological security of nine mining cities in Anhui Province. The multiplicative normalization method was used to combine the optimized G1 and CRITIC weighting methods to achieve subjective and objective weight assignment. Then, the VIKOR model was used to consider the group effect and individual compromise based on compromise programming, and the difference of measured values of different weight indexes was taken into account. Finally, an obstacle degree model was used to diagnose the obstacle factors. [Results] The G1-CRITIC-VIKOR model under the interaction of multiple indicators produced results that were well matched with the actual data. The nine mining cities in Anhui Province were ranked (from high to low) based on their soil and water ecological security levels as Chizhou, Xuancheng, Chuzhou, Tongling, Ma'anshan, Suzhou, Bozhou, Huaibei, and Huainan. The proportion of workers and peasants employed, the matching coefficient of water and soil resources, the per capita water consumption, the proportion of land reclamation, and the per capita disposable income were the key factors restricting the level of water and soil ecological security of mining cities in Anhui Province. [Conclusion] The mining cities in Anhui Province should actively carry out ecological civilization construction and strive to transform their economies into intensive economies. At the same time, afforestation efforts should be implemented for ecological restoration and reconstruction of damaged mining areas so as to ensure the scientific and reasonable mining of coal resources on the basis of ecological security of water and soil.